2009
DOI: 10.1021/jf900963p
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Theaflavin Gallates and Thearubigins by Acceleration of Catechin Oxidation in a New Fermented Tea Product Obtained by the Tea-Rolling Processing of Loquat (Eriobotrya japonica) and Green Tea Leaves

Abstract: In a project to produce a new fermented tea product from non-used tea leaves harvested in the summer, we found that kneading tea leaves ( Camellia sinensis ) with fresh loquat leaves ( Eriobotrya japonica ) accelerated the enzymatic oxidation of tea catechins. The fermented tea obtained by tea-rolling processing of tea and loquat leaves had a strong, distinctive flavor and a plain aftertaste, which differed from usual black, green, and oolong teas. The phenolic constituents were similar to those of black tea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…26,27) However, their biological activities have not been fully evaluated because of difficulties with supply of pure compounds, due to the complexity of black tea polyphenols. Our results provide a facile and efficient method for preparation of pure theasinensins.…”
Section: Biomimetic One-pot Preparation Of a Black Tea Polyphenol Thementioning
confidence: 99%
“…26,27) However, their biological activities have not been fully evaluated because of difficulties with supply of pure compounds, due to the complexity of black tea polyphenols. Our results provide a facile and efficient method for preparation of pure theasinensins.…”
Section: Biomimetic One-pot Preparation Of a Black Tea Polyphenol Thementioning
confidence: 99%
“…Fresh green tea leaves are particularly rich in catechin (CTN) which constitutes 30-45% of solid green tea extract (Tanaka et al ., 2009). In addition, CTN is a major, abundant flavonoid present in grape seed and black tea (Yilmaz and Toledo, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto et al [22] demonstrated that THSNs A-G (THSNs F/G are dimers of ECG-EGCG) are components of oolong tea. Nonaka et al [23] and Tanaka et al [24] demonstrated the presence of THSNs A and B in mildly oxidized green tea (at 0.061% of total tea leaf weight and 0.5% of dry tea leaf weight, respectively). EGCG and EGC, predominant catechins present in green tea, are present at 4–12% and 2–6%, respectively, of the dry leaf weight [2526].…”
Section: Introductionmentioning
confidence: 99%